Stabilisation and Rebalancing with Fiscal or Monetary Devaluation: A Model-Based Comparison - Lukas Vogel (Center for Economic Studies and ifo Institute (CESifo), 2015)
The paper uses a small open economy general-equilibrium model to compare fiscal and nom-inal exchange rate devaluation with respect to their impact on economic activity and the cur-rent account. In particular, it investigates to which extent fiscal devaluation mimics nominal exchange rate adjustment and mitigates the output loss associated with demand rebalancing and external adjustment. The results suggest that internal or external devaluation can support external adjustment and mitigate its impact on economic activity, without leading to lasting adjustment themselves. The quantitative contribution of a tax shift from labour to consump-tion as standard example of fiscal devaluation remains moderate, however.
Keywords: E52; F41; F47; 330; devaluation; exchange rate; tax shift; recession; rebalancing